Ask a New Question
Search
Questions and answers by
Kuai
Questions (1)
Hank and Rashad are walking the Appalachian Trail from Maine southward through Maryland for a distance of 1164 miles. They have
1 answer
540 views
Answers (951)
-33 + m = 10 -33 +33 + m = 10 + 33 m = 43
AC^2 = AB^2 + BC^2 AC^2 = 3^2 +4^2 AC = 9 + 16 AC^2 = 25 AC = sq(25) = 5
Total sales = 4400/2% + 100000 = 220000 + 100000 Ksh 320000 No of sold = 320000/500 = 640
s^2+-2) t^3+4 s^0 t^7 = t^7
Cos = sin(90 - 2x) Sin(x + 60) = sin(90 - 2x) x + 60 = 90 - 2 x 3x + 60 = 90 3x = 30 x = 10 Tan(x + 60) tan(10 + 60) tan(70) = 2.747
-3x-4y =20 x-10y= 16 -3x -4y = 20 3x -30y = 48 -34y = 68 y = -2 x - 10(-2) = 16 x + 20 = 16 x = -4
alpha = a= 0.05 Z0.025 = 1.96 p = 0.5 q = 1-p = 0.5 E = 0.05 Effect size = 384.16 n = 385
P(x < 113) mean = 125 Standard deviation = sqrt(variance) Standard deviation = 5 z = (113-125)/5 z = -12/5 z = -2.4 P ( z < -2.4) = 0.0082
1. C 2. D 3. B 4. A
z = (score -mean)/sd z = (2500 -2500)/500 z = 0 is 50%
(x + 79 + 84 + 68)/4 = 80 (x + 231)/4 =80 x +231 = 320 x + 231- 231 = 320-231 x = 89 Fourth test 89
x = liters of 37% acid solution Other = (50 - x) = liters of 27% solution 37x + 27*(50 - x) = 50*36 37x + 1350 - 27x = 1800 10x = 450 x = 45 liters 45 liters of 37% acid and 5 liters of 27% acid.
Adult: a Children: c a + c = 450 70a + 40c = 27750 Substitute c = 450 -a 70a + 40(450 - a) = 27750 70a + 18000 -40a = 27750 30a + 18000 = 27750 30a + 18000- 18000= 27750-18000 30a = 9750 30a/30 = 9750/30 a = 325 c = 450 -a c = 450-325 c = 125
1. 2x(10x) = 20x^2 2. You can check because if -3m(m + 8) -3m(m-8) = -3m^2 + 24m 3. 4d(2d - 9) = -8d^2 - 36d
13a + 9b -2a -4b 13a -2a + 9b - 4b = 11a + 5b
Exp = 1(.35) + 2(.4) + 3(.1) + 4(.15) = .35 + .8 + .3 + .6 = 2.05 Variance = 1^2 (.35) + 2^2(.4) + 3^2(.1) + 4^2(.15) = .35 + 1.6 + .9 + 2.4 = 5.25 Sd = sqrt(5.25-(2.05)^2) = 1.02
Phat = 500/1200 phat =0.4167 E = 1.96 * sqrt(.4167*.5833/1200) E = 0.0279 0.4167 -+ 0.0279 [0.3888, 0.4446]
(1+x/x^3)dx = x -1/x + c
-15- (3-7) + 6 *(-2) +(-8) -9 = -15-(-4) +(-12) - 8 -9 =-15 + 4 -12 -8 -9 = -11 -12 -8 -9 =- -40
27 -18/3 * (-4)-0-33-(-39) 27-6* (-4) - 0 - 33 -(-39) =27 + 24 -0 -33 + 39 =51-33 + 39 = 5$
80 * .2 16
37, 38, 39, 41, 43, 47, 52, 54 Yes
6 * 10 = 60 (60-y)/9 = 5 60-y = 45 60-45 = y 15 = y The value of the score that was removed 15
Z = (score-mean)/SD -1.7 = (13-18.1)/SD -1.7 = -5.1/SD -1.7SD = -5.1 SD = -5.1/-1.7 SD = 3.0
Oj: x Apple juice: (8-x) .25x + .75(8-x) = .4(8) .25x + 6 -.75x = 3.2 6 -0.5x = 3.2 -.5x = 3.2-6 -.5x = -2.8 x = 5.6
Mean = np = 25(.2) = 5 Standard deviation = sqrt((25 * .2*.8)) = 2
A = p( 1 + r/n)^t*n t = 3.5*2 = 7 r = 0.08/2 = 0.04 A = 25000( 1+ 0.04)^7 A = 25000( 1.04)^7 A = $32,898.29
y = mx + b f(x) = 2m + b = 1 f(x) = 4m + b = 0 f(x) = 6m + b = -1 -1(2m + b = 1) 4m + b = 0 -2m -b = -1 4m + b = 0 2m = -1 m = -1/2 2(-1/2) + b = 1 -1 + b = 1 -1+ 1 + b = 1 + 1 b = 2 y = mx +b y = -1/2x + 2
c = 10n + 26 n = 27 n = 39 n = 43 c = 10 ( 27) + 26 c = 270 + 26 c = 296 so you can finish the rest.
20/36
(1- .98)/2 = .01 = 2.33
There is typo for simple interest Simple interest. =Prt = 32500(.069)(3) =$6,727.50 Amount. = p + interest A = $ 32500 + $6727.50 A = 39,227.50
a) annually A = p(1+ r)^t A = 32500(1+ 0.069)^3 A = 32500(1 .069)^3 A = $39,702.37 b) semiannually A = p(1+ r/n)^tn A = 32500(1 + 0.069/2)^(3*2) A = 32500(1.0345)^6 A = $39,835.14 c) quarterly A = p(1+ r/n)^tn A = 32500( 1+ 0.069/4)^(3*4) A =
A = p(1 + r)^t 60000 =p(1.03)^30 60000 = 2.427262471p P = $24719.21
Range = max -min Range =102 -77 Range = 25 Standard deviation = 8.56
n = (z/2 )^2 * pq/E^2 n = (1.96)^2 *0.82*0.18/0.04^2 n = ?
6^x = 6^2 x = 2 2^x = 2^2 x = 2 3^x = 3^4 x = 4 ok
m = (-20-(-11))/(5-2) m = -9/3 m = -3 y -(-11) = -3(x -2) y + 11 = -3x + 6 y + 11 -11 = -3x + 6 -11 y = -3x - 5
Yes
(x - 3)^2 = 22 x - 3 =-+√(22) 3-√(22), 3+√(22)
P(1+ r/n)^tn 8000(1+.12/2)^2*2 8000(1.06)^4 =?
6^x = (1/6)^2 6^x = 6^-2 x = -2 3^x = 8 Log3^x = log8 x log3 = log8 x = log8/log3
bracelet = x Necklace = 5x x + 5x = 192 6x = 192 6x/6 = 192/6 x = 32 Necklace = 5x = 5(32) = 160
y-1/x+3=-3/4 y-1/x+ 1/x + 3-3 = -3/4 + 1/x -3 y - 0 + 0 = -3/4 - 3 + 1/x y = (-3 - 12)/4 + 1/x y = -15/4 + 1/x
A = l*w l = 2w -1 120 = (2w-1)w 120 = 2w^2 -w 2w^2 -w -120 = 0
Adult: x Student: y x + y = 90 12x+ 8y = 980 12x +8(90-x) = 980 12x + 720 -8x = 980 4x = 260 x = 65 y = 25
0/2, 4/12, 2/3, 5/6, 9/9
You're welcome.